2021
DOI: 10.1093/eurjpc/zwab171
|View full text |Cite
|
Sign up to set email alerts
|

Statin therapy and lipoprotein(a) levels: a systematic review and meta-analysis

Abstract: Aims  Lipoprotein(a) [Lp(a)] is a causal and independent risk factor for cardiovascular disease (CVD). People with elevated Lp(a) are often prescribed statins as they also often show elevated low-density lipoprotein cholesterol (LDL-C) levels. While statins are well-established in lowering LDL-C, their effect on Lp(a) remains unclear. We evaluated the effect of statins compared to placebo on Lp(a) and the effects of different types and intensities of statin therapy on Lp(a). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 65 publications
1
25
0
1
Order By: Relevance
“…An ILLUMINATE trial showed that Lp(a) levels are positively and dose-dependently correlated with atorvastatin dosage [ 9 ]. De Boer et al reported that statins are associated with approximately 1.1 mg/dL increases in Lp(a) levels compared to placebo, whereas high-intensity statins are associated with 2.6 mg/L increases in Lp(a) levels [ 29 ]. Several systematic reviews and meta-analyses most recently indicated that statins increase Lp(a) levels by 10–20% [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…An ILLUMINATE trial showed that Lp(a) levels are positively and dose-dependently correlated with atorvastatin dosage [ 9 ]. De Boer et al reported that statins are associated with approximately 1.1 mg/dL increases in Lp(a) levels compared to placebo, whereas high-intensity statins are associated with 2.6 mg/L increases in Lp(a) levels [ 29 ]. Several systematic reviews and meta-analyses most recently indicated that statins increase Lp(a) levels by 10–20% [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, kits that aim to quantify the mass concentration of Lp(a) are more prone to variation compared to molarity-measuring tests, leading to diverging values of different mass-targeting kits, even within the same population with a standard Lp(a) molar concentration [ 60 , 61 ]. Despite this issue and the apo(a)-insensitive quantifying methods, [ 61 , 62 ] commercial kits measuring Lp(a) in mg/dL instead of estimating its molarity in nmol/L are still amply encountered in practice and the literature [ 63 , 64 ]. Moreover, converting the mass concentration of Lp(a) to its molar equivalent (mg/dL to nmol/L) cannot produce accurate results, although attempts have been made and a rough 2–2.5× conversion factor has been proposed [ 65 ].…”
Section: Measurement Of Plasma Lp(a) Concentration and Standardizationmentioning
confidence: 99%
“…According to recent evidence, conflicting data exist regarding the effect of statins on Lp(a). Although statins remain one the most effective and safest drug category for primary prevention of ASCVD, a recent study revealed a mean 11% increase in Lp(a) levels with their use [ 63 , 243 , 244 ]. Moreover, the ILLUMINATE trial revealed that, in high-risk CVD patients, Lp(a) levels are positively and dose-dependently correlated with atorvastatin dosage [ 245 ].…”
Section: Lp(a)-lowering Treatmentmentioning
confidence: 99%
“…In an individual-patient data meta-analysis of statin-treated patients, associations of baseline and on-statin treatment Lp(a) with CVD risk were approximately linear, with an increased risk at Lp(a) values equal to or greater than 30 mg/dL for baseline lipoprotein(a) and equal to or greater than 50 mg/dL for on-statin Lp(a) [ 56 ].…”
Section: Lipoprotein (A) (Lp(a))mentioning
confidence: 99%